Cross-sectional study of patients with axial spondyloarthritis fulfilling imaging arm of ASAS classification criteria: baseline clinical characteristics and subset differences in a single-centre cohort - Bubová, Kristyna; Forejtová, Šárka; Zegzulková, Kateřina; Gregová, Monika; Hušáková, Markéta; Filková, Mária; Hořínková, Jana; Gatterová, Jindřiška; Tomčík, Michal; Szczuková, Lenka; Pavelka, Karel; Šenolt, Ladislav (BMJ open, 2019)
OBJECTIVE: This study compared demographic, clinical and laboratory characteristics between patients with radiographic and non-radiographic axial spondyloarthritis (axSpA). METHODS: In this single-centre cross-sectional study, a total of 246 patients with axSpA fulfilling the imaging arm of Assessment of SpondyloArthritis International Society classification criteria were recruited. A total of 140 patients were diagnosed as non-radiographic axial spondyloarthritis (nr-axSpA), and 106 patients had ankylosing spondylitis (AS). Sociodemographic characteristics, disease manifestations, clinical and laboratory disease activity and their differences between subsets were analysed. P values below 0.05 with CI 95% were considered statistically significant. RESULTS: More nr-axSpA patients were women (61.4%) compared with 24.7% of AS patients. First symptoms developed earlier in AS patients compared with nr-axSpA (23.0 (IQR 17.5-30.0) vs 27.8 (IQR 21.0-33.7) years, p=0.001). Disease manifestations did not differ, but patients with nr-axSpA experienced peripheral arthritis more frequently (35.7% vs 17.0%, p=0.001) with less hip involvement (8.6% vs 18.9%, p=0.022) compared with patients with AS. Patients with AS exhibited worse spinal mobility and physical function compared with nr-axSpA. AS Disease Activity Scores and CRP levels were significantly higher in patients with AS compared with nr-axSpA (2.4 (IQR 1.7-2.8) vs 2.0 (IQR 1.1-2.3), p=0.022 and 7.1 (IQR 2.6-14.9) vs 2.5 (IQR 0.8-8.2) mg/L, p<0.001, respectively). CONCLUSIONS: Our data demonstrated some known and also novel differences between the two imaging arm fulfilling axSpA subgroups. Non-radiographic patients were mostly women who had experienced shorter disease duration, milder disease activity and better functional status with less hip involvement but more peripheral arthritis compared with patients with AS.
Keywords: disease activity; Sex Factors; ankylosing spondylitis; ankylózující spondylitida; Humans; spondylartritida; Radiography; Spondylarthritis; C-reaktivní protein; prevalence; radiografie; kohortové studie; spondyloarthritis; Female; dospělí; Range of Motion, Articular; lidé; společnosti lékařské; sexuální faktory; tělesná a funkční výkonnost; Cohort Studies; Adult; Physical Functional Performance; Spine; ženské pohlaví; stupeň závažnosti nemoci; Male; Spondylitis, Ankylosing; non-radiographic axial spondyloarthritis; Cross-Sectional Studies; Severity of Illness Index; Prevalence; Societies, Medical; rozsah kloubních pohybů; mužské pohlaví; páteř; C-Reactive Protein; průřezové studie